Penerapan Metode Struktural Analitik Sintetik Sebagai Upaya Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas II SD Inpres Tamarunang - Nur Annisa; Tarman A. Arif; Muhammad Saeful (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The main problem in this research is how to improve initial reading ability by applying the Synthetic Structural Analytical method to class II students at SD Inpres Tamarunang. This research aims to improve initial reading skills using the Synthetic Structural Analytical method in class II students at SD Inpres Tamarunang.This type of research is class action research (PTK) which consists of 2 cycles, each of which is carried out in 3 meetings. Research procedures consist of planning, implementing actions, observing and reflecting. The subjects in this research were 23 class II students at SD Inpres Tamarunang. The research instruments used were observation sheets (students and teachers), evaluation test sheets. The data collection techniques in this research are observation and tests. The data collected is then analyzed using qualitative analysis.The results of the research showed that after using the SAS method, grade 2 students at SD Inpres Tamarunang had improved their initial reading skills in cycle I. The initial data percentage of completeness was 47.82% or 11 students out of 23 and an average score of 70%. In cycle II there was an increase in the number There were 19 students who reached the KKM out of 23 students or 82.60% completed. Based on the results of the research above, it can be concluded that the application of the Synthetic Structural Analytical method can improve reading skills at the beginning of class II at SD Inpres Tamarunang.